2011
DOI: 10.1590/s1516-635x2011000400002
|View full text |Cite
|
Sign up to set email alerts
|

Corn texture and particle size in broiler diets

Abstract: The objective of this study was to evaluate the effect of corn texture and the particle size on broiler performance, carcass yield, nutrient digestibility, and digestive organ morphometrics. In Experiment I, 720 male Cobb chicks were distributed in a completely randomized experimental design with a 2 x 3 factorial arrangement, consisting two corn textures (dented and hard) and three corn particle sizes, was applied, with four replicates of 30 birds each. Corn particle size was classified according to geometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
6
12
1
1
Order By: Relevance
“…The lower weights of the empty crops in broilers fed the coarse diets indicate less feed accumulation in the crop compared with those fed the fine diets. Our current study's finding of greater relative gizzard weights in broilers fed the coarse diets compared with those fed the fine diets is supported by other recent research (Benedetti et al., 2011 ; Bhuiyan et al., 2012 ; Rodgers et al., 2012 ; Jacobs and Parsons, 2013 ). Jacobs and Parson ( 2013 ) reported 47 and 22% heavier gizzards in broilers fed whole sorghum and coarse corn, respectively, compared to those fed fine diets.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The lower weights of the empty crops in broilers fed the coarse diets indicate less feed accumulation in the crop compared with those fed the fine diets. Our current study's finding of greater relative gizzard weights in broilers fed the coarse diets compared with those fed the fine diets is supported by other recent research (Benedetti et al., 2011 ; Bhuiyan et al., 2012 ; Rodgers et al., 2012 ; Jacobs and Parsons, 2013 ). Jacobs and Parson ( 2013 ) reported 47 and 22% heavier gizzards in broilers fed whole sorghum and coarse corn, respectively, compared to those fed fine diets.…”
Section: Discussionsupporting
confidence: 89%
“…Our current study's finding of greater protein digestibility with coarse particles is also in accordance with findings of recent broiler studies (Pacheco et al., 2013 ; Liu et al., 2013 ). This improved digestibility may be attributed to a more functional gizzard and increased gastric reflux between proventriculus and gizzard that result in more time for gastric enzyme activity and even for more protease activity in the duodenum (Benedetti et al., 2011 ). Pacheco et al.…”
Section: Discussionmentioning
confidence: 99%
“…The result was consistent with the findings by Benedetti et al. (), who reported that hard corn resulted in higher DM digestibility and lower nitrogen excretion, and consequently higher performance in 42‐day‐old broilers. Particle size was also involved in the influence of corn endosperm type on broiler performance, with the coarser‐ground hard corn providing the best FCR (1.88) around marketing age.…”
Section: Discussionsupporting
confidence: 92%
“…Particle size determination of ground corn showed differences in particle size distribution between hard and dent corn passed through the same screen size in the same hammer mill. Consistent with previous reports (Benedetti et al, 2011), grinding hard corn resulted in coarser particles compared with the dent. This may be due to differences in endosperm hardness between the corn types, because the particle size of milled grains is affected by grain hardness (Dobraszczyk et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…on AME n of corn in broilers. From 1 to 42 d of age, the type of corn endosperm in diets fed to broilers did not influence growth performance, although there were some large numerical differences that were not significant but favoured corn with a harder endosperm (Benedetti et al, 2011). et al (2001) concluded that the type of endosperm (hard or soft) had little effect on broiler production and effects on feed intake and gain appeared to be influenced more by production environment.…”
Section: Vitreousnessmentioning
confidence: 99%